Application of plasma mass spectrometry for half-life measurement of medium and long-lived radionuclides. (December 2020) - Braysher, Emma; Russell, Ben; Read, David
Abstract: When combined with established primary counting techniques, atom counting using inductively coupled plasma mass spectrometry (ICP-MS) can be a powerful metrological tool for providing updated, precise half-life values for medium and long-lived radionuclides, giving end-users increased confidence in measurement for a range of nuclear applications. ICP-MS is increasingly being used for this application, and this study outlines the methods for atom counting using the latest generation tandem ICP-MS/MS. The aim is to provide a consistent methodology that is currently lacking, and attention is paid to the importance of interference removal and minimising uncertainties, with preliminary results given for uranium isotopes.